Hydrogen production and COD elimination rate in a continuous microbial electrolysis cell: The influence of hydraulic retention time and applied voltage. Issue 2 (27th February 2012) - Escapa, A.; Lobato, A.; García, D.M.; Morán, A.
<x xml:space="preserve">Abstract</x> The influence of the applied voltage (Vapp) and the hydraulic retention time (HRT) on hydrogen and methane production and the removal rate for chemical oxygen demand (COD) was studied in a membrane‐less microbial electrolysis cell with a Ni‐based cathode. When a synthetic effluent from a dark‐fermentation process was fed continuously into the anodic chamber, an increase in both the Vapp (from 0.6 to 1.0 V) and HRT (from 8 to 12 h) increased the hydrogen production rate from 0.18 to 1.42 L LA−1 d−1 (liters per liter of anode per day) and the COD elimination rate from 46 to 94%. The influences of Vapp and HRT on hydrogen production and the COD removal rate were found to be interdependent. Whereas acetic and butyric acids were easily degraded, propionic acid exhibited pseudo‐recalcitrant behavior. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 263‐268, 2013